PEGylated Recombinant Human Growth Hormone Jintrolong® Exhibits Good Long-Term Safety in Cynomolgus Monkeys and Human Pediatric Growth Hormone Deficiency Patients - Wu, Wei; Zhou, Juan; Wu, Chuandong; Zhou, Qian; Li, Xiaoyu; Zhang, Yanlin; Zuo, Conglin; Yin, Jun; Hou, Ling; Wang, Shuyang; Gao, Hongyang; Luo, Tianhong; et al. (Frontiers in Endocrinology, 2022)
Jintrolong® is a long-acting PEGylated recombinant human growth hormone (PEG-rhGH) developed for weekly injection in patients with pediatric growth hormone deficiency (PGHD). Although PEG modification of therapeutic proteins is generally considered to be safe, concerns persist about the potential for adverse vacuolation in tissues of long-term exposure to PEG-included therapies, especially in children. We assessed the safety of Jintrolong® in cynomolgus monkeys with examination of vacuolation in brain choroid plexus (CP) and also reported long-term clinical safety data obtained from children with PGHD. The toxicity of Jintrolong® was assessed following 52-week administration with doses at 0.3, 1 or 3 mg/kg/week. The levels of vacuolation of CP in animals were dose-dependent and at least partially reversible after a 104- or 157-week recovery period. Vacuolation in the CP epithelium did not lead to obviously subcellular structural or cell functional abnormalities. Compared to the clinical dose of 0.2 mg/kg/week Jintrolong® in PGHD patients, exposure in monkeys under NOAEL 3 mg/kg/week exhibited safety margins greater than 120.5, the predicted minimum dose to induce vacuolation in monkeys is equivalent to 1.29 mg/kg/week in human, which is 6.45-fold higher than clinical dose. The safety data acquired in clinical trials for Jintrolong® were also analyzed, which include phase III (360 patients), phase IV (3000 patients) of 26-week treatment and a follow-up study with treatment lasting for 3 years. There was no statistically significant difference in the incidence of adverse reactions between Jintrolong® group and daily rhGH control group (no PEG), and no new adverse effects (AE) were observed in Jintrolong® group at the clinical therapeutic dose level of 0.2 mg/kg/week.